2022
DOI: 10.3390/foods11111638
|View full text |Cite
|
Sign up to set email alerts
|

Large Yellow Tea Extract Ameliorates Metabolic Syndrome by Suppressing Lipogenesis through SIRT6/SREBP1 Pathway and Modulating Microbiota in Leptin Receptor Knockout Rats

Abstract: Metabolic syndrome is a chronic metabolic disorder that has turned into a severe health problem worldwide. A previous study reported that large yellow tea exhibited better anti-diabetic and lipid-lowering effects than green tea. Nevertheless, the potential mechanisms are not yet understood. In this study, we examined the prevention effects and mechanisms of large yellow tea water extract (LWE) on metabolic syndrome using leptin receptor knockout (Lepr−/−) rats. Seven-week-old male Lepr−/− and wild type (WT) li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 84 publications
(98 reference statements)
3
6
0
Order By: Relevance
“…In this study, we exhibited that homogeneous LYT polysaccharides (LYPs) could prevent diet-induced obesity and metabolic syndrome via improving glucolipid homeostasis, increasing energy expenditure, modulating islet β-cell function, and reducing M1 polarization of ATMs and inflammatory responses in C57BL/6J mice. Consistent with the previous studies demonstrating the anti-obesity efficacy of LYT, 23,24 our results confirmed that the oral administration of LYPs remarkably reduced HFD-induced body weight gain and visceral fat mass. Obesity-related metabolic syndrome is accompanied by hyperglycemia, hyperlipidemia, and hyperinsulinemia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we exhibited that homogeneous LYT polysaccharides (LYPs) could prevent diet-induced obesity and metabolic syndrome via improving glucolipid homeostasis, increasing energy expenditure, modulating islet β-cell function, and reducing M1 polarization of ATMs and inflammatory responses in C57BL/6J mice. Consistent with the previous studies demonstrating the anti-obesity efficacy of LYT, 23,24 our results confirmed that the oral administration of LYPs remarkably reduced HFD-induced body weight gain and visceral fat mass. Obesity-related metabolic syndrome is accompanied by hyperglycemia, hyperlipidemia, and hyperinsulinemia.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the previous studies demonstrating the anti-obesity efficacy of LYT, 23,24 our results confirmed that the oral administration of LYPs remarkably reduced HFD-induced body weight gain and visceral fat mass. Obesity-related metabolic syndrome is accompanied by hyperglycemia, hyperlipidemia, and hyperinsulinemia.…”
Section: Discussionsupporting
confidence: 92%
“…It is important to research new applications of tea flowers for improving the economic value thereof. Large-leaf yellow tea (LYT) is one kind of yellow-type tea which has multiple health benefits, such as alleviating alcoholic liver disease and inhibiting adipose tissue hypertrophy ( Xu et al., 2021 ; Wang et al., 2022 ; Wu et al., 2022 ). However, LYT is made from old tea leaves and stems, leading to poor aroma and flavor or being unpopular.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, a previous study showed that GEBE increased the abundance of Faecalibaculum and thereby ameliorated early atherosclerosis in mice (Liu et al, 2021). In addition, the abundance of Faecalibaculum was previously reported to be closely and negatively associated with characteristics of the metabolic syndrome (Wu et al, 2022a). Lactobacillus, a recognized probiotic, ameliorates glucose metabolism disorders and disturbances of the intestinal ecology in a rat model of T2D and reduces inflammation and the circulating concentration of lipopolysaccharide (El-Baz et al, 2021;Wu et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%